2021
DOI: 10.1155/2021/9998558
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Response and Failure Model of Thin Plate Rock Mass under Impact Load

Abstract: The layered rock mass widely exists in mining, construction, transportation, and water conservancy projects, and the damage phenomena of plate crack and spalling often occurs in the process of coal and rock dynamic disaster in deep mining. Therefore, the rock mass nearby excavation surface is usually considered to be composed of layers of thin plate rock mass to reveal the damage and failure mechanism of rock mass. In the whole dynamic process of mining and coal and rock dynamic disaster, rock mass would bear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The extreme values of the amplitude curves of these three action points showed two stages as follows: rst increasing and then decreasing; the vibration curves of 2# and 4# action points reached the peak after 2.25 cycles, and that of 6# action point the peak after 1. 25 Effective vibration modes and predominant frequency of interface vibration under impact load. Based on Hilbert Huang transform (HHT), the interface vibration waveforms were decomposed by EEMD [20][21][22][23],…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme values of the amplitude curves of these three action points showed two stages as follows: rst increasing and then decreasing; the vibration curves of 2# and 4# action points reached the peak after 2.25 cycles, and that of 6# action point the peak after 1. 25 Effective vibration modes and predominant frequency of interface vibration under impact load. Based on Hilbert Huang transform (HHT), the interface vibration waveforms were decomposed by EEMD [20][21][22][23],…”
Section: Resultsmentioning
confidence: 99%
“…combined with energy formula: , the energy distributions and marginal spectrum of the decomposed waveforms were obtained [24][25].…”
Section: Resultsmentioning
confidence: 99%
“…These dynamic effects lead to obvious vibration at the interfaces, which is a key factor leading to dynamic damage and failure of coal and rock mass [13][14][15][16]. Meanwhile, Li et al demonstrated that the initial location of damage and failure can be determined by the lowest frequency effective vibration mode [17]. These articles illustrate that the study of coal rock vibration signals can help to initially reveal the vibration response characteristics of the coal rock interface under impact loading.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the limitation of the research subjects of the isotropic plastic materials, this works only considered the thickness distortion and ignored the inherent capability of width distortion. Based on the framework, Li et al [27] further expanded the application scope to obtain the similarity of isotropic elastic-plastic coupling situation. Meanwhile, Davey et al [28] developed a scaling system with width and thickness distortion for isotropic and anisotropic elastic materials based on equation analysis method.…”
Section: Introductionmentioning
confidence: 99%